Synthesis, structure and electrical properties of Mg-, Ni-codoped bismuth niobates - M. S. Koroleva; I. V. Piir; E. I. Istomina (Chimica Techno Acta)
Mg-, Ni-codoped bismuth niobates Bi1.6Mg0.8-xNixNb1.6O7-δ (x = 0; 0.2; 0.4; 0.6; 0.8) were obtained by conventional solid-state reaction method. It was shown that the Mg atoms are distributed at the Nb sites while the Ni atoms are distributed over the Bi- and the Nb-sites, according to the results of comparison of pycnometric and X-ray density of the Bi1.6Mg0.4Ni0.4Nb1.6O7-δ pyrochlore. In this case, about 15–20% of the vacancies are formed at the Bi sites. The obtained compounds are stable up to their melting point based on the DSC analysis data. Real dielectric permittivity ε' of the Bi1.6Mg0.8-xNixNb1.6O7-δ samples decreases from 80 to 65 with the temperature decrease from 25 to 700 °C and practically does not depend on frequency in the range of 1–1000 kHz. Oxides Bi1.6Mg0.8-xNixNb1.6O7-δ behave like insulators up to 280 °C, their conductivity increases with temperature (Ea,dc ≈ 1.3 eV, dc) and with the Ni content at a given temperature.